Survey of public interest in cycling during the Covid-19 pandemic - Ipnu Ibrahim; Mas’odi Mas’odi; Moh. Hasan Basri (Universitas Sriwijaya, 2021)
The purpose of this research is to see the number of people's interest in cycling. Survey and interview methods were conducted to obtain research data. Respondents taken are people who do cycling at Taman Bunga Sumenep with a total of 25 respondents. The results of the study show data that 75% of respondents think that cycling is very useful and very interested during the Covid-19 pandemic. From the results of this study, it can be concluded that public interest in cycling is very high and based on observations made during the study, cycling is currently the right sport to do during the Covid-19 pandemic.